PROTOTYPE IoT-BASED AIRFIELD LIGHTING ON/OFF MONITORING SYSTEM (ALMOS) USING ESP32 MICROCONTROLLER - Andeni, Afra Nabilah (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2025)
Airfield Lighting (AFL) systems play a crucial role in ensuring safe aircraft operations, particularly during low visibility, night operations, and adverse weather conditions; however, at Radin Inten II Lampung Airport, inspections are still conducted manually, relying on visual observation that often leads to delays in detecting lamp failures, longer maintenance times, and increased operational costs. This study aims to design and develop a prototype of an IoT-based Airfield Lighting On/Off Monitoring System (ALMOS) capable of real-time monitoring of AFL lamp status to improve maintenance efficiency and reliability. Using the Research and Development (R&D) method with a simplified Borg and Gall model, the prototype integrates the ACS712-30A current sensor to detect electrical flow, the Arduino Uno ATMega328P for initial data processing, and the Power Line Carrier Communication (PLCC) KQ330 module as a medium for transmitting data through existing power lines, while the ESP32 microcontroller receives and displays the data on a web-based monitoring interface. The experimental results show that ALMOS accurately detects current variations corresponding to on/off conditions and transmits data stably via PLCC and Wi-Fi networks, proving its effectiveness in real-time monitoring. The novelty of this research lies in the integration of IoT and PLCC technologies to simulate advanced systems like AGLAS into a simpler, low-cost, and educational prototype. This study contributes to airport engineering technology by providing a scalable reference model for developing automated AFL monitoring systems that enhance operational efficiency, minimize manual inspections, and serve as a practical learning medium for aviation technology students.